2020
DOI: 10.3389/fpsyg.2020.587871
|View full text |Cite
|
Sign up to set email alerts
|

Active Music Engagement and Cortisol as an Acute Stress Biomarker in Young Hematopoietic Stem Cell Transplant Patients and Caregivers: Results of a Single Case Design Pilot Study

Abstract: This paper reports the results of a single case design pilot study of a music therapy intervention [the Active Music Engagement (AME)] for young children (age 3.51 to 4.53 years) undergoing hematopoietic stem cell transplantation (HCST) and their caregivers. The primary aims of the study were to determine feasibility/acceptability of the AME intervention protocol and data collection in the context of HCST. Secondary aims were to examine caregivers' perceptions of the benefit of AME and whether there were chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Methods for this trial are grounded in our previously published work including several pilot studies [33][34][35][36] and a manuscript that details of our treatment fidelity strategies [37].…”
Section: Methodsmentioning
confidence: 99%
“…Methods for this trial are grounded in our previously published work including several pilot studies [33][34][35][36] and a manuscript that details of our treatment fidelity strategies [37].…”
Section: Methodsmentioning
confidence: 99%
“…Music experiences (songwriting, instrumental improvisation) were used to teach and reinforce new knowledge and skills. Other programs have incorporated parent instruction, music resources, and ongoing projects to encourage uptake and independent use of music as a support strategy (Barry et al, 2010; Holochwost et al, 2020; Lindenfelser et al, 2012; Robb et al, 2014, 2017).…”
Section: Music Therapy and The Psychosocial Standards Of Carementioning
confidence: 99%
“…Stress experienced by children and AYAs with cancer and their caregivers is highly interrelated. Studies have documented parent-reported benefit from witnessing improvements in their child or AYAs mood, engagement, and overall well-being as result of music therapy services (Docherty et al, 2013; Robb et al, 2014, 2017; Yates et al, 2018), with recent trials investigating development of dyadic interventions to directly address the interrelated needs of caregivers and their children (Holochwost et al, 2020; Robb et al, 2017; Yates et al, 2018).…”
Section: Music Therapy and The Psychosocial Standards Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…2 Apart from this, patients also experience feelings such as fear, isolation, and depression during the treatment process. 3 It has been accepted for years that the stress that is experienced affects patients and their informal caregivers (ICs) throughout the disease process involving comprehensive care. 4 It was reported that, in proportion to the symptom load of the patient, ICs experienced even more stress than patients.…”
mentioning
confidence: 99%